Стратегічні аспекти виведення нового товару на ринок - Кобєлєв, Валерій Миколайович; Прошутя, Олена Сергіївна (НТУ "ХПІ", 2016)
У статті розглядаються питання виведення нового товару на ринок. Розглянуто етапи за якими відбувається вихід нових товарів на ринок. Показано необхідність проведення маркетингових досліджень випущених марок товарів для своєчасної заміни застарілих. Особливу увагу приділяється основним типам стратегій конкурентної боротьби при виході з новими товарами на ринок. Також розглянуто фактори успіху нового продукту на ринку.

The article deals with the withdrawal of the new product on the market. The urgency of the matters dealt with in the article due to several reasons. Among the most important reasons are: globalization, ever increasing demands of consumers and the information society. This leads to the need to constantly update products that made the company and improving existing marketing strategies.It is proposed that the development and bringing to market new products campaigns should pay attention not only to the product but also the entire chain "need - consumer - product - market". Each of the components is a potential new sales. The stages which is out new products to market and analyzes the major types of competitive strategies of the company. The important point is that the company in its development process can gradually change its competitive strategy. There are three main approaches to the definition of "new product." Based on analysis of these approaches can conclude that it is necessary to apply a comprehensive approach in deriving a new product to market. The necessity of marketing research products issued stamps for the timely replacement of obsolete. Also the success factors of a new product on the market.
Strategic aspects of the release of the new product on the market
Keywords: товар новий; стратегія; ринок; ризик; маркетинг; дослідження; new product; strategy; market; risk; marketing; research